(3GdEaUGM Yf EYQGH CHjGJ eTcdI GdEjVGMs - (3CHhfUQ GdMSf Hf CSO Hf GdMSf GdaGQbj,J (B487 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEffj CWGd Gddg HbGAc deG hbaJ Ydi TQja efRdJc hefja QJHJc s
(3BNQgG (B:s
(3Ndjdj Efj HGdYdG LO YGdb fgGQj hJWjjfj EdjgG GdeSGYjG hbO LYdfG eG ChVMfG ef Pdc hGdSHb dfG aj JSgjd hYQgG heG ShGgG aeWQM eROhd s
(3GfXQ GdLRA GdChd (B15 (3fMh hagQSJ HGSe(B: (3GdEaUGM aj GdYhjUs
(3QJH GdeDda GdCHjGJ Ydi MQha GdeYLe hgj fSNI ebGHdI hHgG fXGe GdJYbjHI hCKQ JbWjYs
(3heUOQ GdeUhQI GdEeGe jMji UfYGA (B2 (3COHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B206s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B43 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B26 s
Keywords: (3GdfMhs